ANALYSIS OF MECHANICAL PROPERTIES OF SS 400 STEEL MATERIAL WITH FCAW WELDING METHOD - unsika, gagat (Universitas Majalengka, 2025)
Welding is a method of joining metals that involves metallurgical bonds at the metal joints by melting some of the parent metal and filler metal with or without additional metal and producing a continuous joint. Tensile strength is one of the things that is very much considered in the selection of a material for industry. SS 400 is a type of carbon steel that has a carbon content of 0.23%. For the repair industry, the most suitable is to use welding (MMAW), but the Flux-Cored Arc Welding (FCAW) process has more advantages and has been appreciated by the industry for years. The tests in this report are tensile and bending tests. In the Tensile test, the highest tensile strength was 567.5 N / mm2 on sample T1, the lowest tensile strength was 570.9 N / mm2 on sample T2 and the average tensile strength value was 569.2 N / mm2. In the Face Bending test, the maximum load on sample F1 is 135,227.00 N, on sample F2 is 131,877.70 N and the average value of the maximum load is 133,552.35 N with the test results being cracks at the joints of samples F1 and F2. In the Face Bending test, the maximum load on sample R1 is 123,828.400 N, on sample R2 is 131,624.40 N and the average value of the maximum load is 127,726.40 N with the test results being cracks at the joints of sample R1 and fractures at the joints of sample R2.